2014
DOI: 10.2169/internalmedicine.53.2720
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Serous Retinal Detachment as a Presenting Sign of Nephrotic Syndrome

Abstract: We herein present a case of bilateral serous retinal detachment (SRD) as a presenting sign of nephrotic syndrome (NS). A 48-year-old man complained of decreased vision related to bilateral SRD. Laboratory tests revealed NS (serum albumin, 17 g/L: proteinuria, 15.40 g over 24 hours). Following treatment for edema with a diuretic, the bilateral SRD resolved completely, with a full recovery of the patient's vision. A kidney biopsy disclosed glomerular and vascular amyloid deposits; the amyloid stained strongly wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…The incidence of this clinical presentation is probably underestimated as it is largely overlooked in these patients. To our knowledge, among the published cases of AL amyloidosis with chorioretinal disease [10][11][12], our case is one of the first to document the rapid progression of fundus alterations and their stabilization after disease remission. Elementary lesions in our case include pachychoroid, large subretinal detachments, which resolved after chemotherapy and subretinal deposits that are hyperautofluorescent leading to masking on angiography.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The incidence of this clinical presentation is probably underestimated as it is largely overlooked in these patients. To our knowledge, among the published cases of AL amyloidosis with chorioretinal disease [10][11][12], our case is one of the first to document the rapid progression of fundus alterations and their stabilization after disease remission. Elementary lesions in our case include pachychoroid, large subretinal detachments, which resolved after chemotherapy and subretinal deposits that are hyperautofluorescent leading to masking on angiography.…”
Section: Discussionmentioning
confidence: 64%
“…These alterations would lead to secondary retinal pigment epithelium (RPE) dysfunction accounting for subretinal detachments and impaired photoreceptor outer segment phagocytosis leading to hyperautofluorescent subretinal material accumulation. The nephrotic syndrome could also have a role in the choroidal changes and subretinal detachments through a modification of the oncotic pressure [12,[17][18][19]. By restoring the plasmatic protein balance and decreasing amyloid deposits, the initiation of the first chemotherapy cycles led to the healing of the nephrotic syndrome and the resorption of the subretinal fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Among the reported cases, some patients had SRD in the macular region [3–8, 10], while other patients had concurrent macular oedema [3, 8] or RPE detachment and tears [4], or the condition manifested as macular oedema alone [9]. Some patients showed concurrent increases in CT on OCT [6]. Patients suffering from these diseases also typically had hypoalbuminaemia, with blood ALB concentrations of 10–23 g/L, which usually resolved after several weeks of treatment with glucocorticoids, immunosuppressants and diuretics [37, 9, 10].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some case reports have shown that patients with NS can have bilateral serous retinal detachment (SRD) [3–8], macular oedema [3, 8, 9] and retinal pigment epithelium (RPE) detachment [4], accompanied by an increased choroidal thickness (CT) [6]. SRD and choroidal thickening may also occur in patients with hypoproteinaemia caused by other diseases, such as protein losing enteropathy [7, 10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation